Collaborative Governance dalam Upaya Peningkatan Layanan Air Minum : Studi pada PDAM Kota Surabaya dan PT Sarana Multi Infrastruktur - Rara Saulina Agatha; Galih Wahyu Pradana (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study aims to analyze the effectiveness of collaborative governance between PDAM Kota Surabaya and PT Sarana Multi Infrastruktur (SMI) in improving drinking water services. The main research question is how this collaborative governance is implemented and what factors influence its effectiveness. Collaborative governance, according to Ansell and Gash's theory, is a joint decision-making process involving public and private sectors to achieve common goals. This approach enables synergy between government and private companies in addressing resource limitations. The research method used is a qualitative approach with a case study, through in-depth interviews, participatory observation, and document analysis. The results show that this collaboration improves the efficiency of clean water distribution, although there are challenges such as differing objectives and resource allocation. Factors such as trust, commitment, and effective communication play a crucial role in the success of the collaboration. The implications of this study highlight the importance of inclusive institutional planning and policy design that supports cross-sector collaboration to strengthen public service provision. This research contributes to the development of the collaborative governance concept in the drinking water supply sector and provides recommendations for government and private sectors to improve the quality of clean water services for the wider community.